2021
DOI: 10.1155/2021/5582245
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Dietary Bioactive Peptides in Redox Balance and Metabolic Disorders

Abstract: Bioactive peptides (BPs) are fragments of 2–15 amino acid residues with biological properties. Dietary BPs derived from milk, egg, fish, soybean, corn, rice, quinoa, wheat, oat, potato, common bean, spirulina, and mussel are reported to possess beneficial effects on redox balance and metabolic disorders (obesity, diabetes, hypertension, and inflammatory bowel diseases (IBD)). Peptide length, sequence, and composition significantly affected the bioactive properties of dietary BPs. Numerous studies have demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 144 publications
(245 reference statements)
0
7
0
Order By: Relevance
“…Protein hydrolysate has recently attracted a lot of interest because of its biological activities, which may have the ability to improve human health and reduce illness risk (43,44). It is well known that the sequence of amino acids governs the different activities of bioactive peptides (7).…”
Section: Discussionmentioning
confidence: 99%
“…Protein hydrolysate has recently attracted a lot of interest because of its biological activities, which may have the ability to improve human health and reduce illness risk (43,44). It is well known that the sequence of amino acids governs the different activities of bioactive peptides (7).…”
Section: Discussionmentioning
confidence: 99%
“…Oat bran is a key by-product and accounts for approximately 50% of the weight of dry oat grains [ 147 ]. Oat bran also contains high-quality proteins such as β-glucan, saponin, albumin, prolamins, and glutelins that lower cholesterol levels ( Figure 13 ) [ 148 , 149 , 150 , 151 , 152 ]. To date, studies on oats mainly assessed the nutritional value and processing characteristics of oat grains or powder [ 13 , 42 , 55 ].…”
Section: Functional Enhancement Using Oat By-productsmentioning
confidence: 99%
“…Enzymatic hydrolysis of the dietary proteins generates BPs, which are short chains of 2–15 amino acids residues, can enhance nutritional value, safety, bioactive function and reduce the allergenicity [ 3 , 4 ]. Numerous studies have demonstrated that BPs with antioxidant activity produced by proteolysis can achieve antioxidation by scavenging free radicals, chelating transition metals, and enhancing the activity of endogenous antioxidant enzymes such as catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px).…”
Section: Introductionmentioning
confidence: 99%
“…A disturbance of balance between oxidants and antioxidants results in oxidative stress. Reactive oxygen species (ROS) are molecules derived from aerobic cellular metabolism; in the oxidative stress condition excessive production of ROS can disrupt the intracellular redox balance and cause numerous diseases such as cancer, diabetes, atherosclerosis, cardiovascular and neurodegenerative [ 4 ]. A growing number of studies have demonstrated that APs from protease hydrolysates can effectively scavenge free radicals or inhibit the production of ROS.…”
Section: Introductionmentioning
confidence: 99%